Observational prospective cohort study of patients with newly-diagnosed ocular sebaceous carcinoma. Issue 1 (31st October 2012) - Muqit, Mahiul M K; Foot, Barny; Walters, Stephen J; Mudhar, Hardeep S; Roberts, Fiona; Rennie, Ian G
Abstract : Purpose: To investigate the epidemiology and clinicopathological management for ocular sebaceous carcinoma (OSC) in the UK. Methods: Observational prospective cohort study of patients with newly-diagnosed OSC. The British Ophthalmological Surveillance Unit captured incident cases of OSC between 2008 and 2010. Incident and 6-month follow-up questionnaires from reporting ophthalmologists captured OSC demographic and clinical data. Results: Data were available on 51 patients with unilateral OSC (response rate 85%). The UK estimated annual incidence was 0.41 cases per million population (95% CI 0.31 to 0.54). Median age was 70 years (SD 14, range 28–98) with 57% women. OSC location was upper lid (54%), lower lid (20%), multicentric (14%) and caruncle (12%). Most common misdiagnoses included chalazion (42%), basal cell carcinoma (30%) and blepharoconjunctivitis (16%), with median delay in diagnosis of 10 months (SD 9, range 0.5–36). Specialist ophthalmic pathologists performed diagnostics in 62%, with pagetoid/intraepithelial spread present in 39%. Misdiagnosis of chalazion (p=0.019) and pagetoid tumour spread (p=0.016) was associated with a significant diagnostic delay (one-way ANOVA/R 2 ). Primary surgical management involved excision with reconstruction (49%), primary exenteration (10%) and Mohs surgery (8%). There were three deaths (out of 51) during the study period; one patient died of OSC-related disease and the other two due to other causes. Conclusions: This population-based prospective study confirms OSC as a rare cancer in the UK. Masquerade syndromes result in significant diagnostic delays and increase the risk of pagetoid tumour spread. There is considerable UK variation in pathological and surgical management, and ocular reconstruction and radical surgery is often required for OSC due to delayed presentation.